Implementasi Metode Analisis Gap Dan Profile Matching Untuk Kelayakan Calon Debitur Di Koperasi Simpan Pinjam (Ksp) Kopdit Solidaritas Santa Maria Assumpta - yelly y nabuasa; Adriana Fanggidae; Derwin R Sina; Arfan Y Mauko (J-Icon : Jurnal Komputer dan Informatika, 2019)
In granting credit to debtors, it must go through an assessment of whether the debtor is appropriate or not feasible. KSP Koprit Solidaritas has set policy standards in granting credit to accept or reject the risk of bad credit, namely assessing prospective borrowers who meet the conditions of character rating, ability to pay off credit, capital owned, collateral owned and socioeconomic conditions. In this study, the design and manufacture of decision support system applications were carried out using profile matching methods to assess the eligibility of prospective debtors. Profile Matching is used to determine the priority with the highest ranking, which is used as a suggestion from the right system in determining the best alternative. The test results using 60 data obtained an accuracy of 81.667% with an error rate of 18.333% which indicates that the decision support system is functioning optimally following the Profile Matching method.